Analysis of The Implementation of Child Protection Law in Combating Violence During Dating in Medan City (Lbh Medan Study) - Selmaria purba; Budi Sastra Panjaitan (Journal Equity of Law and Governance, 2024)
Currently, there are many cases of violence against children during dating, but some of those who experience these cases are reluctant to report to the authorities to be assisted in resolving the problem. However, there are also those who report but the handling often cannot be resolved. Basically, violence against girls has been regulated in the Law. The problems that we want to explore in this study are what causes violence against children during dating in the city of Medan. How is the implementation of the Child Protection Law in overcoming violence against children during dating? What is done by LBH Medan in providing protection to children who are victims of violence during dating in the city of Medan. This study uses empirical legal research, namely research or observation based on facts that occur in the field with a criminal anthropology approach method. Data collection was obtained through field research by means of interviews, while secondary data through library research. The results of the study that the author obtained were that there were many factors that caused violence in dating in girls, namely weak parental supervision, the absorption of foreign culture which caused teenagers to fall into promiscuity and the rapid development of technology, while based on the annual report from the National Commission on Violence Against Women in 2023, it was stated that the number of cases of violence in dating was ranked first, violence in dating reached 3,528 (three thousand five hundred and twenty eight).